2021
DOI: 10.3390/ijerph18168654
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Hamstring Extensibility on Sagittal Pelvic Tilt, Sagittal Spinal Curves and Recurrent Low Back Pain in Team Sports Players: A Gender Perspective Analysis

Abstract: It is assumed that mechanical restriction of hamstring tightness disrupts sagittal spine–pelvis–leg alignment and alters the lumbar–pelvic rhythm predisposing to low back pain (LBP) in athletes; however, this association is not clear. A prospective cross-sectional cohort study was conducted to determine the influence of hamstring extensibility (HE) on sagittal pelvic tilt, sagittal spinal curves, and LBP in 94 soccer and basketball players (61 man and 33 woman) with (n = 36) and without recurrent LBP (n = 58).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 93 publications
(154 reference statements)
0
14
1
Order By: Relevance
“…Previously published studies have determined the lower extremity flexibility profile by applying the ROM-SPORT battery to handball [30], soccer [15,31], futsal [17,32], and inline hockey players [18,29]. In addition, the ROM-SPORT battery predicted the risk of low back pain using the hip flexion test with the knee extended in basketball and soccer players [33], the external and internal rotation test in inline hockey players [34] and hip adduction and knee flexion in equestrian athletes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies have determined the lower extremity flexibility profile by applying the ROM-SPORT battery to handball [30], soccer [15,31], futsal [17,32], and inline hockey players [18,29]. In addition, the ROM-SPORT battery predicted the risk of low back pain using the hip flexion test with the knee extended in basketball and soccer players [33], the external and internal rotation test in inline hockey players [34] and hip adduction and knee flexion in equestrian athletes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar curvatures in the slump sitting and trunk forward bending positions, together with height, have been recently found as predicting factors of sciatica history in female classical ballet dancers [ 32 ]. Recurrent lower back pain has been related to the lumbar curve during trunk flexion, as well as reduced hamstring extensibility [ 33 , 59 ]. Hamstring length and demands are factors to consider in future analyses of rowers.…”
Section: Discussionmentioning
confidence: 99%
“…McGregor et al [ 61 ] found that rowers with lower back pain had significantly less range of motion at the L5/S1 level (in the ‘catch’ position: 7.5 ± 1.3° in normal; 4.8 ± 1.2° in previous history of lower back pain groups; and 2.8 ± 5.5° in current lower back pain group). Recently, Cejudo et al [ 59 ] found a relationship between lower back pain and static functional lumbar hyperkyphosis, and structured hyperlordosis in male and female team sports players.…”
Section: Discussionmentioning
confidence: 99%
“…Limited range of motion (ROM) due to a lack of muscle flexibility has been shown to be one of the most important predictors of common sports injuries, such as groin pain (restricted hip abduction [ 9 , 10 , 11 ], lateral rotation [ 9 ], medial rotation [ 12 , 13 ], and total rotation [ 9 ] ROMs); tendinopathies of the patella (restricted hip flexion with the knee extended [ 10 , 12 , 14 ] and ankle dorsiflexion ROMs [ 15 , 16 ]) and Achilles (restricted ankle dorsiflexion ROM [ 17 ]); strains of the hamstrings (restricted hip flexion with the knee extended [ 18 , 19 ], knee flexion [ 18 ], and ankle dorsiflexion ROMs [ 20 ]) and quadriceps (restricted knee flexion ROM [ 18 , 19 ]); rupture of the anterior cruciate ligament (restricted lateral [ 21 , 22 ] and medial hip rotation ROMs [ 21 , 23 , 24 ]); low back pain (restricted hip flexion with the knee extended [ 25 , 26 ], hip extension [ 27 ], hip lateral rotation [ 28 , 29 ], hip internal rotation [ 26 , 29 ], and knee flexion [ 30 ] ROMs) and knee pain (restricted hip extension [ 31 ] and flexion ROMs [ 32 ]). In addition, certain sports such as taekwondo, diving, figure skating, and gymnastics require high ROM values in order for athletes to successfully perform the technical actions most highly rated by the judges [ 33 ] and improve their physical performance [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It therefore seems clear that ROM should be assessed in athletes as an intervention strategy to optimise their athletic performance and reduce their risk of injury. Flexibility has been shown to be specific to each joint, muscle action, or specific movement [ 25 , 26 ]. For this reason, the assessment of flexibility in athletes has shown very different results depending on the sport [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%